Response of pearl millet (Pennisetum glaucum) to crop residue application and potassium management options under rainfed condition - KUMAR, ASHOK; RANA, K S; BANA, R S; DASS, ANCHAL; MEENA, M C; KUMAR, SARVENDER; GOURAV, RAJ KUMAR; SHANKAR, KRIPA (The Indian Journal of Agricultural Sciences, 2024)
A field experiment was conducted during rainy (kharif) seasons of 2021 and 2022 at ICAR-Indian Agricultural Research Institute, New Delhi to study the impact of crop residue mulching and potassium management options on growth and yield attributes of pearl millet [Pennisetum glaucum (L.) R. Br]. The experiment was conducted in a split plot design (SPD) with three mains plots, viz. C0, No residue mulching; C1, Crop residue mulching @3 t/ha; and C2, Crop residue mulching @3 t/ha + Pusa decomposer; and five potassium management in sub plot, viz. K0, No potassium application; K1, 40 kg K2O/ha; K2, 40 kg K2O/ha + potassium solubilising bacteria (KSB); K3, 30 kg K2O/ha + KSB; and K4, 20 kg K2O/ha + KSB. Pearl millet variety Pusa Composite 701 was used for the experiment. Significant variation among growth and yield parameters were observed under crop residue as well as potassium management options. Under crop residue mulching these were recorded maximum in treatment C2 (crop residue mulching @3 t/ha + Pusa decomposer). However, under potassium management options plant height (11.8–13.3%), ear head length (9.5 and 9.8%) and yield (26.7 and 24%) of pearl millet was recorded maximum in treatment K2 (40 kg K2O/ha + KSB) during the consecutive year over the control. These finding highlights the synergistic effects of potassium and residue management demonstrating that the presence of KSB enhanced potassium uptake by the plants, resulting in improved outcomes.